8(y+5)+y=2(y+5)-8

Simple and best practice solution for 8(y+5)+y=2(y+5)-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(y+5)+y=2(y+5)-8 equation:



8(y+5)+y=2(y+5)-8
We move all terms to the left:
8(y+5)+y-(2(y+5)-8)=0
We add all the numbers together, and all the variables
y+8(y+5)-(2(y+5)-8)=0
We multiply parentheses
y+8y-(2(y+5)-8)+40=0
We calculate terms in parentheses: -(2(y+5)-8), so:
2(y+5)-8
We multiply parentheses
2y+10-8
We add all the numbers together, and all the variables
2y+2
Back to the equation:
-(2y+2)
We add all the numbers together, and all the variables
9y-(2y+2)+40=0
We get rid of parentheses
9y-2y-2+40=0
We add all the numbers together, and all the variables
7y+38=0
We move all terms containing y to the left, all other terms to the right
7y=-38
y=-38/7
y=-5+3/7

See similar equations:

| 10+0.07s+9s=15s | | 3×-y+5=10 | | 10w=28+3w | | 4x-7+110=14x-7 | | 2^x=8^3^+^5x | | 6x–8=-20 | | -2(w-5)=|0-3|+5w | | y2-12y+52=5 | | -9+v=-16 | | 16d+5=-10 | | 52-z=37 | | 8(-x+7)=-16 | | -5j=-35 | | 5x-8-2x=9-x=3 | | |6w+4|=9 | | 0=-2(y-5) | | 8t=-64 | | (7x+3)+24=(12x+2) | | -5(4x-5)=-20x+25 | | –7n−9=9−4n | | 4x-7+100=14x-7 | | x/4=x/7-9 | | 3x+9=2x+4x | | 9x-13=-32 | | (4x-1)(3x-8)=180 | | s+9=-6 | | 1/4a+10=-7 | | 7(8n-3)=315 | | 7x–16=-23 | | 55x+83x=66 | | 2y-7=y;8 | | 5/12y=1/3 |

Equations solver categories